The Impact of Telegraphic Cue Activities on EFL Iraqi Pupils’ Production - Abd, Nahla Mahmoud; Saleh, Madeha Saif Al-Deen (Journal of Tikrit University for Humanities, 2025)
While the importance of English as an international language cannot be overstated, Iraqi pupils need to develop skills for creative communication in both spoken and written forms; however, many pupils struggle with fluency and creativity due to insufficient exposure to effective teaching strategies. In this regard, Telegraphic Cue Activities play a crucial role as they may exploit the natural tendencies of learners in using cues composed largely of content words. However, the effect of Telegraphic Cue Activities on creative communication has not been significantly investigated in the Iraqi context. The current study, therefore aims to identify the impact of TCA on Iraqi EFL pupils’ written and spoken production and to test the hypothesis that hypnotized that There is no statistically significant difference in the experimental group of EFL Iraqi pupils who are engaged in TCA in their spoken and written communication than in the control group who are not. Following a quasi-experimental treatment, 60 fourth-year preparatory female pupils, consisting of an equal number of pupils from Al-Khansaa Preparatory School for Girls, Kirkuk, were equally divided into experimental and control groups. Pupils in the experimental group received Telegraphic Cue Activities-based classes while those in the control group followed conventional communicative courses. Both groups were administered a validated achievement test in both components of creative communication before and after treatment. The results revealed that Telegraphic Cue Activities are effective for spoken language development, as they significantly enhanced the pupils’ oral creative expression, whereas only a negligible improvement was noted in the written communication of the pupils, which shows that written communication needs extra supplementary support. The study therefore recommends that Telegraphic Cue Activities-based lessons should be integrated into the EFL instructional plan to promote oral creativity, accompanied by a different set of writing approaches to enhance written communication.